PERAN ISTRI SEBAGAI WANITA KARIR DALAM MEWUJUDKAN KELUARGA SAKINAH STUDI KASUS DESA TUMPANG KECAMATAN TUMPANG KABUPATEN MALANG - Indah Savira Dorojatul Hikmah; Khoirul Asfiyak; Moh. Muslim (Jurnal Hikmatina, 2022)
Women are half of the community, even women are also a male partner in living household life. The study of women is quite interesting to investigate until this era. The family is a domestic group that is bound to each other by marriage and legal ties. As for the research used by the researcher, it uses a qualitative approach and the type of research is a case study. The main results of this study are about the factors that cause a wife to choose a role as a career woman and the steps of a wife as a career woman in realizing a sakinah family. Besides that, here we also discuss the positive and negative impacts of the wife's role as a career woman